Enabling Failure-resilient Intermittently-powered Systems Without Runtime Checkpointing - Chen, Wei-Ming; Hsiu, Pi-Cheng; Kuo, Tei-Wei (Proceedings of the 56th Annual Design Automation Conference 2019, 2019)
Self-powered intermittent systems enable accumulative execution in unstable power environments, where checkpointing is often adopted as a means to achieve data consistency and system recovery under power failures. However, existing approaches based on the checkpointing paradigm normally require system suspension and/or logging at runtime. This paper presents a design which enables failure-resilient intermittently-powered systems without runtime checkpointing. Our design enforces the consistency and serializability of concurrent task execution while maximizing computation progress, as well as allows instant system recovery after power resumption, by leveraging the characteristics of data accessed in hybrid memory. We integrated the design into FreeRTOS running on a Texas Instruments device. Experimental results show that our design achieves up to 11.8 times the computation progress achieved by checkpointing-based approaches, while reducing the recovery time by nearly 90%.CCS CONCEPTS* Computer systems organization → Embedded software; Reliability; * Computing methodologies → Concurrent algorithms;